Systemic vasculopathy associated with an RNF213 p.Arg4810Lys variant in moyamoya disease: A review - Duk-Kyung Kim; Shin Yi Jang; Sung-A Chang; Taek Kyu Park (Precision and Future Medicine, 2022)
Moyamoya disease (MMD) is a steno-occlusive disease of the distal cerebral arteries. Ring finger protein 213 (RNF213) p.Arg4810Lys is a susceptibility gene of MMD for which related vasculopathies are not well characterized. Heterozygous patients were mostly asymptomatic or exhibited isolated MMD. Homozygous patients showed a very unique pattern of diffuse narrowing of the entire aorta along with stenosis of the splanchnic, renal, coronary, iliofemoral, and/or peripheral pulmonary arteries, regardless of presence or absence of MMD. RNF213 p.Arg4810Lys is associated with high penetrance of systemic vasculopathy in homozygous patients and low penetrance of intracranial stenosis, i.e., MMD, in heterozygous patients, which suggests a gene-dosage effect.